THE CHARACTER OF LOUISA CLARK’S IN THE ME BEFORE YOU MOVIE : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Titis Setyabudi; Astri Mutia Elshinta Devi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
The objective of this research were to find out the character of Louisa Clark’s in the Me Before You movie based on individual psyhology by Alfred Adler. This research use qualitative method to analyze the data. The source data of the research focus on captures from the movie, actions, and sounds or dialogues that describe the character of Louisa Clark. The result of this research showed that there six principles namely, fictional finalism, inferiority feeling, striving of superiority, social interest, style of life, and creative self.